2012
DOI: 10.1097/qad.0b013e32835192ae
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporotic fracture risk associated with cumulative exposure to tenofovir and other antiretroviral agents

Abstract: Cumulative exposure to TDF and, among protease inhibitors, LPV/RTV was independently predictive of increased risk of osteoporotic fracture in the HAART era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
216
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(222 citation statements)
references
References 22 publications
2
216
2
2
Order By: Relevance
“…Young children, especially Tanner Stage 1 and 2, are at higher risk for decreased BMD [42,43]. Cumulative exposure to tenofovir has been associated with an increased risk of fractures in adults [44], which may explain cases of fractures reported in children. However, not all studies of tenofovir in children have identified a decline in BMD [23,45,46].…”
Section: Discussionmentioning
confidence: 96%
“…Young children, especially Tanner Stage 1 and 2, are at higher risk for decreased BMD [42,43]. Cumulative exposure to tenofovir has been associated with an increased risk of fractures in adults [44], which may explain cases of fractures reported in children. However, not all studies of tenofovir in children have identified a decline in BMD [23,45,46].…”
Section: Discussionmentioning
confidence: 96%
“…Although this difference was not significant, the results are not unexpected due to the negative impact of protease inhibitors on tenofovir-related kidney or bone toxicity. 23,24 The small sample size of the abacavir-lamivudine group is a limitation of the study. However, the only existing data on the combination abacavir/lamivudine plus raltegravir included 35 antiretroviral-naive patients, and thus the number of patients with this combination of interest was almost double in our study.…”
Section: Discussionmentioning
confidence: 99%
“…L'esposizione prolungata ad alti livelli plasmatici di TFV è associata a disfunzione tubulare e circa lo 0,3% dei pazienti in terapia con TDF può sviluppare una sindrome di Fanconi (7), una condizioni rara caratterizzata da una disfunzione del tubulo renale prossimale che altera il trasporto di aminoacidi, glucosio, fosfato, acido urico, sodio, potassio, bicarbonato e proteine (8). L'utilizzo di TDF è notoriamente correlato anche a riduzione della densità minerale ossea nell'anca e nella colonna, tramite un aumentato turnover osseo, correlato anche alla perdita di fosfati dovuta alla tossicità tubulare (9)(10)(11)(12). Descriviamo di seguito il caso di un paziente coinfetto HIV-1/HBV in esiti di sindrome di Fanconi TDF-correlata e affetto da un'iniziale osteonecrosi della testa del femore sinistro, trattato con E/C/F/TAF con miglioramento della funzionalità renale e completa regressione dell'osteonecrosi femorale, con un anno di follow-up.…”
Section: L'unclassified